Game Based Financial Planning Simulator for Elementary School Students - Samuel Slamet Santosa, Donald (Institut of Shanti Bhuana, 2024)
This research departs from the low level of financial literacy among Generation Z today. Based on several preliminary studies that have been conducted previously, it was found that financial literacy in Generation Z is lower than in the millennial generation, which means there is a decline in the ability to manage finances. To prevent further decline in financial literacy among society in the future, financial management skills, especially those related to financial planning, need to be developed from an early age. The aim of this research is to develop a game-based financial planning simulator that can help teachers and parents instill financial understanding in students at the elementary school level. A simulator in the form of a game that can provide enthusiasm and motivation for students to plan their finances well. This research is development research (Research and Development) which uses the ADDIE development model (analyze, define, develop, implement and evaluate). The analysis stage is carried out by collecting financial planning models that already exist and then developing them at the define and develop stages. At the implementation stage, pretest-posttest experimental research was conducted on students in 2 elementary schools in Central Java. The collected data was tested for differences using the t-test. The experimental results become material for the final evaluation stage so that it becomes the final model. The result of this research is a product in the form of a game which is a student financial planning simulator based on Roblox. After going through a pretest-posttest experiment testing process, it was found that the game had effectively succeeded in increasing students' financial literacy, especially in terms of financial planning.